Assessment of Hepatic Enzyme Derangements in Patients with Covid-19 - Asma Nafisa; Saifullah, Sarah Naheed; Riwa Amjad; Mehwish Iqbal (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
About half of the patients with Covid-19 have deranged hepatic enzymes at presentation. The goal of the study was to identify specific patterns of abnormalities in enzymes so that clinical treatment and therapeutic methods can be improved for affected individuals. This understanding is crucial for improving patient outcomes and creating individualized treatment schedules. A total of 182 RT-PCR-confirmed Covid-19 cases were enrolled and different biochemical variables were compared among patients with varying degrees of disease severity. Data with abnormal distribution were described as median (minimum-maximum) and analyzed with the Mann-Whitney U test and the Kruskal-Wallis test. Multivariate binary regression analysis was applied to find the predictors associated with disease severity. The mean age of patients was 56.46 ± 15.60 years. Median AST levels in 182 patients were more than ALT at admission (52.45 vs. 46.35 U/L. Most of the subjects with the deranged hepatic enzyme at presentation had minimal elevations 1-2X upper limit of normal (ALT 74.8%, AST 77.0%, TBIL 98.3%). An increase of ≥ 5 times the upper limit of normal was observed in 7 (3.8%) and 5 (2.7%) patients for AST and ALT, respectively. Non-survivors were older, had higher median levels of AST 70 U/L vs. 47 U/L, LDH 855 vs 470 (for both p-value = 0.0001), and had a longer hospital stay compared to discharged groups. In multivariate analysis, advanced age, raised level of LDH and extended hospital stay showed a significant association with mortality. Liver dysfunction is commonly observed in hospitalized subjects and may be linked to severe disease.